2017
DOI: 10.3390/su9020237
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Household Heterogeneity Factors on the Green Travel Behavior of Urban Residents in the East China Region

Abstract: A questionnaire survey was conducted with 1475 urban residents in the east region of China to explore the impact of household heterogeneity factors on the green travel behavior of urban residents. The green travel behavior was divided into practice-based and promotion-based green travel behavior, and the results showed that variables including gender, age, educational background, household monthly income, amount of cars, professional status, positional tiers and housing ownership were correlated with both of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
(51 reference statements)
1
16
1
Order By: Relevance
“…However, contrary to expectation, hypothesis 5a and 6a were not supported. These results are somewhat different from those of other studies [18,[93][94][95], which suggested that females are more sensitive to green behavior. This study showed that there is no gender gap in the relationship between (1) overall image and word-of-mouth intentions and (2) overall image and willingness to pay more in an environmentally friendly airline context.…”
Section: Theoretical Implicationscontrasting
confidence: 57%
See 1 more Smart Citation
“…However, contrary to expectation, hypothesis 5a and 6a were not supported. These results are somewhat different from those of other studies [18,[93][94][95], which suggested that females are more sensitive to green behavior. This study showed that there is no gender gap in the relationship between (1) overall image and word-of-mouth intentions and (2) overall image and willingness to pay more in an environmentally friendly airline context.…”
Section: Theoretical Implicationscontrasting
confidence: 57%
“…López-Mosquera [94] tried to examine gender differences the willingness to pay for the conservation of the park using 200 samples and the data analysis result indicated that females have stronger the willingness to pay for the conservation of the park. More recently, Yang et al [95] collected data from 1475 urban residents in order to identify the influence of personal demographic characteristics on green travel behavior. The results of data analysis showed that green travel behavior is more important to females than males.…”
Section: The Moderating Role Of Gendermentioning
confidence: 99%
“…[8]. With rapid economic development and the expansion of urbanization, car pollution can result in serious consequences without proper management.…”
Section: Green Travelmentioning
confidence: 99%
“…The second group consists of practitioners across different disciplines; included, traffic engineers, police officers and driving institute instructors. According to GGDM's purposive sampling, fourteen (14) participants have been involved; where eight (8) of them were academician and the remaining six (6) were practitioners. The GGDM method is able to overcome the logistical difficulties in arranging a specific time with involved decision makers and in saving the cost of managing the decision-making sessions.…”
Section: Fw(a Imentioning
confidence: 99%
“…Therefore, the existing in-vehicle driving assistance systems and simulators lack the incorporation of driver's behaviors on reducing energy consumption. Travel behavior is the interaction between people and transport, which impacts to fuel consumption and CO 2 emission [13,14]. Recently, travel behavior researchers have created a new term called driver behavior, which considerably contributes to reducing fuel consumption and CO 2 emission.…”
Section: Introductionmentioning
confidence: 99%